Analisis studi empiris tentang efektivitas mindfulness-based stress reduction untuk burnout perawat di rumah sakit: Kajian literatur - Sulistianingsih, Ike; Tallutondok, Eva Berthy (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Burnout is a common problem experienced by hospital nurses due to high work pressure, characterized by emotional exhaustion, depersonalization, and decreased personal accomplishment. Mindfulness-Based Stress Reduction (MBSR) is an approach proven effective in addressing work burnout. Purpose: To determine the effectiveness of mindfulness-based stress reduction on nurse burnout. Method: A literature review of 13 studies meeting all inclusion criteria and 791 studies were excluded from scientific articles published between 2020 and 2025, evaluating the effectiveness of MBSR in hospital nurses. The literature search was conducted through PubMed, ScienceDirect, ProQuest, and CINAHL, following PRISMA guidelines with search keywords tailored to Medical Subject Headings (MeSH): (